The Palm Oil Industry in Nigeria and Malaysia: Decline and Economic Sustainability - Shehu, Sani; Afandi Salleh, Mohd (International Journal of Oil Palm, 2023)
Oil palm is a west African crop. The trade in palm oil has emerged during the industrial revolution led by Britain, this palm oil was used to lubricate machines. In 1960s, Nigeria was the largest producer of palm oil globally, which accounted for the 43% of palm oil production entirely, but then the entire production declined due to some factors that slowed the palm oil production growth. While in Malaysia, oil palm production serves as the leading and contributing sector to its economy; and it also achieved recognition globally. Palm oil has made a huge contribution to Malaysia economic growth by providing employment, improving infrastructure, alleviating poverty, and generating income for workers and government. This paper objective is to explore the Nigerian decline and Malaysian sustainability on palm oil. It is a qualitative paper, it used primary and secondary method to collect data. The primary method used open-ended interview to collect data, while the secondary method used documents such as: books, journal, conference papers to collect data; and it employed inductive thematic analysis for analysing the interview data collected. It used ATLAS.ti 8 software to help analyse the data. The finding is Nigerian decline which includes: oil boom in 1970s and decline in agriculture, civil war, and traditional palm oil production; and Malaysian sustainability on palm oil includes: environmental consciousness, economic escalation, and social commitment. In conclusion, Nigeria has to learn from Malaysian sustainability to recover its production.